Analisis Insiden Fatality Akibat Covid-19 Menggunakan Metode 5 Why, SCAT, BowTie, dan Interpretive Structural Model (ISM) - Dewayani Nur Wijayanti; Tatan Sukwika; Soehatman Ramli (Jurnal Migasian, 2022)
Abstract. The research in general aims to analyze the fatality incident due to Covid-19 that occurred on March 28, 2021 using a combined method of 3 root cause methods, namely the SCAT, 5 Why, and Bow Tie methods, and ends by prioritizing improvements with the Interpretive Structural Model method ( ISM) And specifically the purpose of this research is to determine the root causes of the main causes using the 5 Why and SCAT methods, Determine the factors before and after the top event that contribute to the threat and consequences of the Covid-19 pandemic risk using the BowTie method, and determine the Barrier factors from BowTie Analysis which are critical factors that must be implemented. The results of the analysis using 5 Whys and PHE SCAT show that there are unsafe actions both from human factors and conditions that cause workers to be exposed to COVID-19 at work sites. To optimize the condition so that it doesn't happen again, a follow-up analysis using BowTie was carried out and the results of the research used ISM (Interpretive Structural Modeling) for critical Barriers for threats (treats) which prioritized to be implemented and monitored, namely A1 (on-site emergency planning). Critical factors Barriers to become (Consequences) that are key to implementation are the main sub-element B2